Change and Continuity in the Role of State Attorneys General in the Obama and Trump Administrations. Issue 3 (18th May 2018) - Nolette, Paul; Provost, Colin
Abstract: During the Trump Administration, state attorneys general (AGs) have become entrenched as integral policymaking actors in the United States. Their expanding policymaking role fits broader patterns of polarized politics, as partisan coalitions of AGs are increasingly willing to sue the federal government, a trend that gathered steam in the Obama Administration and has reached a crescendo in Trump's first year. However, state AGs do cooperate, particularly in corporate litigation to address allegedly widespread, illegal behavior. Utilizing a comprehensive dataset of multi-state lawsuits and Supreme Court amicus briefs, we identify continuity and change in how AGs have employed their powers, by examining their activities during the first year of the Trump presidency and placing these activities in the context of previous administrations. This analysis is accompanied by a pair of case studies, one on conflictual AG environmental litigation and another on bipartisan efforts to address the opioid epidemic. Both demonstrate AG's prominent policymaking power, a power unlikely to abate anytime soon.